Design of a Bike-Bus Network for a City of Half a Million Citizens - De Oliveira, Stefano P. [UNESP]; Luche, José Roberto D. [UNESP]; Marins, Fernando A. S. [UNESP]; Da Silva, Aneirson F. [UNESP]; Costa, Antônio F. B. (American Society of Civil Engineers (ASCE), 2021)
This work develops a mathematical model for designing bikeway networks that integrate into public bus transport services in urban areas using concepts from network multiobjective optimization and mixed-integer linear programming (MILP). The proposed model maximizes 14 objectives and 14 constraints by referring in a generalized way to lane comfort, safety, path objectivity, network connectivity, intermodality with bus service, and monetary budgets. In the context of a developing country, we believe that this model can address the transit network design problem (TNDP) as an innovative proposal for integration between alternative modes of transport and buses. A case study in Sao Jose dos Campos city, Sao Paulo state, Brazil, is conducted, and exact solutions are obtained with partially connected networks (first approach) and fully connected networks (second approach). A scenario analysis enables verification of the integrated transportation system performance and, for the case study, prioritizes the least expensive bikeway type. Therefore, the results from the proposed model can contribute to urban planning in testing alternative scenarios for bike-bus networks.
Keywords: Bike-bus network; Connectivity; Intermodality; Mathematical model; Transit network design problem